Enhancing Confidence and Coping with Stigma in an Ambiguous Interaction with Primary Care: A Qualitative Study of People with COPD. (2nd September 2020) - Lundell, Sara; Wadell, Karin; Wiklund, Maria; Tistad, Malin
Abstract: Meaningful and high-quality interactions between people with COPD and healthcare professionals are essential to accomplish effective and efficient self-management. This study's aim was to explore how people with COPD experience COPD-related interactions with healthcare professionals in primary care, and how these interactions influence their self-management and how they cope with their disease. Interviews were performed with eight women and five men with COPD, and grounded theory guided data collection and analysis. The analysis resulted in a theoretical model and the core category (Re)acting in an ambiguous interaction, representing a dynamic process in which healthcare priorities, healthcare professionals' attitudes and participants' personal emotions were important for the participants' experiences of interactions, and how they managed and coped with their disease. Mutually respectful and regular relationships with healthcare professionals, along with a personal positive view of life, empowered and facilitated participants to accept and manage their disease. In contrast, experiences of being deprioritized and not taken seriously, along with experiences of fear and stigma, disempowered and inhibited participants in making healthcare contacts or forced them to compensate for experienced insufficiencies in primary care. In order to facilitate meaningful and high-quality interactions and enhance patient-provider partnerships in primary care, there is a need to improve the status of COPD, as well as to increase competence in COPD management among healthcare professionals and support the empowerment of people with COPD. Findings from this study could guide the implementation of improved self-management support in primary care for COPD and other chronic conditions.